The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1021/jacs.5b08547
|View full text |Cite
|
Sign up to set email alerts
|

Singlet–Triplet Splittings in the Luminescent Excited States of Colloidal Cu+:CdSe, Cu+:InP, and CuInS2 Nanocrystals: Charge-Transfer Configurations and Self-Trapped Excitons

Abstract: The electronic and magnetic properties of the luminescent excited states of colloidal Cu(+):CdSe, Cu(+):InP, and CuInS2 nanocrystals were investigated using variable-temperature photoluminescence (PL) and magnetic circularly polarized luminescence (MCPL) spectroscopies. The nanocrystal electronic structures were also investigated by absorption and magnetic circular dichroism (MCD) spectroscopies. By every spectroscopic measure, the luminescent excited states of all three materials are essentially indistinguish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

60
405
2
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 215 publications
(471 citation statements)
references
References 61 publications
(140 reference statements)
60
405
2
4
Order By: Relevance
“…46 However, recent work has unambiguously demonstrated that the PL in CP CIS QDs originates from the radiative recombination of a delocalized CB electron with a hole localized on a Cu + ion. 31,47,48 Nevertheless, the nature of the hole localization process (i.e., self-trapping onto a regular Cu + ion 48 or capture by a native defect, such as Cu In 2– ) has yet to be unravelled. 31 …”
Section: Results and Discussionmentioning
confidence: 99%
“…46 However, recent work has unambiguously demonstrated that the PL in CP CIS QDs originates from the radiative recombination of a delocalized CB electron with a hole localized on a Cu + ion. 31,47,48 Nevertheless, the nature of the hole localization process (i.e., self-trapping onto a regular Cu + ion 48 or capture by a native defect, such as Cu In 2– ) has yet to be unravelled. 31 …”
Section: Results and Discussionmentioning
confidence: 99%
“…Upon photoexcitation, the 1S holes nonradiatively moved from the valence band to the impurity in the core 30. The luminescence of the g‐QDs is attributed to the radiative recombination of the conduction band 1S electrons with the impurity holes 30.…”
Section: Resultsmentioning
confidence: 99%
“…24,25 Furthermore, impurity doping of perovskite thin films has been shown to improve their performance in solar cells. 2628 Recently, Mn 2+ doping in colloidal CsPbCl 3 perovskite NCs has been achieved by a direct synthesis method, in which PbCl 2 and MnCl 2 precursors were mixed in the desired ratio, leading to NCs with the characteristic Mn 2+ emission.…”
Section: Introductionmentioning
confidence: 99%